PENGARUH INTANGIBLE ASSET , DEBT TO EQUITY RATIO , DAN RETURN ON ASSET TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018 - Eka Wulandari; Risal Rinofah; Mujino Mujino (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2020)
This study aims to analyze (1) The Effect of Intangible Assets on Firm Value. (2) The Effect of Debt to Equity Ratio on Firm Value. (3) The Effect of Return on Assets on Firm Value (4) and the effect of Intangible Asset, Debt to Equity Ratio, and Return on Assets Simultaneously Against the Firm Value in Manufacturing Companies Listed on the Indonesia Stock Exchange Period 2014-2018. This study uses a sample of 15 companies selected based on criteria, including companies that use the rules of the sharia system and experience profits in a predetermined period. Date analysis used was purposive sampling technique using multiple linear regression tests. The results of this study are positive and significant influences on the intangible asset variable on firm value, the variable debt to equity ratio has a negative and not significant effect on firm value, return on assets has a positive and significant effect on firm value, and the last is intangible assets, debt to equity ratio and return on assset influence jointly or simultaneously on the company’s value.